A Headset Method for Measuring the Visual Temporal Discrimination Threshold in Cervical Dystonia. (18th July 2014) - Molloy, Anna; Kimmich, Okka; Williams, Laura; Quinlivan, Brendan; Dabacan, Adriana; Fanning, Aisling; Butler, John S.; O'Riordan, Sean; Reilly, Richard B.; Hutchinson, Michael
Background: The visual temporal discrimination threshold (TDT) is the shortest time interval at which one can determine two stimuli to be asynchronous and meets criteria for a valid endophenotype in adult-onset idiopathic focal dystonia, a poorly penetrant disorder. Temporal discrimination is assessed in the hospital laboratory; in unaffected relatives of multiplex adult-onset dystonia patients distance from the hospital is a barrier to data acquisition. We devised a portable headset method for visual temporal discrimination determination and our aim was to validate this portable tool against the traditional laboratory-based method in a group of patients and in a large cohort of healthy controls. Methods: Visual TDTs were examined in two groups 1) in 96 healthy control participants divided by age and gender, and 2) in 33 cervical dystonia patients, using two methods of data acquisition, the traditional table-top laboratory-based system, and the novel portable headset method. The order of assessment was randomized in the control group. The results obtained by each technique were compared. Results: Visual temporal discrimination in healthy control participants demonstrated similar age and gender effects by the headset method as found by the table-top examination. There were no significant differences between visual TDTs obtained using the two methods, both for the control participants and for the cervical dystonia patients. Bland–Altman testing showed good concordance between the two methods in both patients and in controls. Discussion: The portable headset device is a reliable and accurate method for visual temporal discrimination testing for use outside the laboratory, and will facilitate increased TDT data collection outside of the hospital setting. This is of particular importance in multiplex families where data collection in all available members of the pedigree is important for exome sequencing studies.